2002
DOI: 10.1016/s0002-9440(10)61102-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Histidine Decarboxylase and Synthesis of Histamine by Human Small Cell Lung Carcinoma

Abstract: We recently found that human small cell lung carcinomas (SCLCs) express, in addition to other neuroendocrine markers, vesicular monoamine transporters. Our present results indicate that SCLCs are histaminergic. We detected the biosynthetic enzyme histidine decarboxylase by immunohistochemistry in paraffin sections of 12 biopsies of SCLC tumors. This finding was supported by immunoblotting and reverse transcription-polymerase chain reaction experiments using established SCLC cell lines, frozen and paraffin-embe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
39
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 19 publications
3
39
0
2
Order By: Relevance
“…In fact, expression of both v-MAT2 and HDC is a feature of histaminehandling cells (Medina et al 2003) and represents a strong indicator of histamine production in NETs from sites different from the stomach. Moreover, such widespread expression of v-MAT2 and HDC in NETs suggests that they may be considered as new general endocrine markers, as previously proposed by other authors (Graff et al 2001(Graff et al ,2002Matsuki et al 2003;Tanimoto et al 2004).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In fact, expression of both v-MAT2 and HDC is a feature of histaminehandling cells (Medina et al 2003) and represents a strong indicator of histamine production in NETs from sites different from the stomach. Moreover, such widespread expression of v-MAT2 and HDC in NETs suggests that they may be considered as new general endocrine markers, as previously proposed by other authors (Graff et al 2001(Graff et al ,2002Matsuki et al 2003;Tanimoto et al 2004).…”
Section: Discussionsupporting
confidence: 61%
“…On the other hand, all available data on IHC expression of HDC in NETs have been obtained using polyclonal antibodies directed against human recombinant L-HDC expressed in E. coli (Graff et al 2002;Matsuki et al 2003;Tanimoto et al 2004), one of which was also employed in the present study. The possibility of a cross-reaction of this antibody with DDC should be considered due to the large PLPdependent domain shared by the two enzymes, which are evolutionary related as they derive from the same ancestor gene (Saenz-de-Miera and Ayala 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest the possibility that HDC may be another marker for neuroendocrine differentiation. One recent study has revealed the expression of HDC in biopsied materials of small cell lung carcinoma (25). To our knowledge, however, no systematic immunohistochemical study of HDC expression in neuroendocrine or endocrine tumors has been reported.…”
mentioning
confidence: 95%
“…Mientras los síndromes endocrinos por producción ectópi-ca de hormonas son frecuentes en los tumores neuroendocrinos pulmonares, especialmente de ACTH, en nuestro caso no se detectó producción ectópica de hormonas, hecho ya descrito en trabajos previos en relación con el carcinoma neuroendocrino de células grandes, aunque sí se detectaron niveles muy elevados de histamina, la cual se ha implicado en alguna ocasión en la patogenia del "flushing" en el síndrome carcinoide asociado a carcinoides gástricos (4) e ileales (5) sintetizada, almacenada y liberada en cultivos celulares de carcinomas de células pequeñas (6).…”
Section: Discussionunclassified